UN R127 PEDESTRIAN PROTECTION ANALYSIS AND OPTIMIZATION OF THE VEHICLE - WANG ShengBo; GE HongJian; YANG Ting; LIU Gang; MA HuiZhen (Jixie qiangdu, 2022)
The regulation UN R127 is the must for the import country since 2018, In order to successfully pass the regulatory certification, so the pedestrian protection performance of the vehicle should be evaluated. In this paper, the pedestrian protection analysis was done by finite method, and the results show that the legform satisfy the regulation, but some area of the head don′t satisfy the requirements of the regulation. So some optimization analysis was made that aimed at the fail area to pass the UN R127 pedestrian protection certification test successfully. Comparing the optimized data of risk points with the experiment, the deviation is 1.9%, which shows the reliability of building the finite element model, and provide reference for the design and development of pedestrian protection for subsequent models.